2012
DOI: 10.1007/s11605-012-1940-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Single-Center Trial Comparing Pancreatogastrostomy Versus Pancreaticojejunostomy After Partial Pancreatoduodenectomy

Abstract: Our randomized controlled trial shows no difference between PG and PJ as reconstruction techniques after partial pancreatoduodenectomy. POPF rate, DGE, and bleeding were not statistically different. Operation time was significantly shorter in the PG group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 53 publications
1
102
1
7
Order By: Relevance
“…[8][9][10][11][12][13][14][15] Some of these com parisons have been summarized in recent systematic reviews and metaanalyses. [16][17][18][19][20] Observational studies sug gested that PG is a safer reconstruction than PJ, resulting in lower morbidity, including lower pancreatic leak rates and decreased postoperative mortality.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Some of these com parisons have been summarized in recent systematic reviews and metaanalyses. [16][17][18][19][20] Observational studies sug gested that PG is a safer reconstruction than PJ, resulting in lower morbidity, including lower pancreatic leak rates and decreased postoperative mortality.…”
mentioning
confidence: 99%
“…La fístula pancrática es la complicación específica más importante de esta intervención puesto que de ella suelen derivar otro tipo de complicaciones como la gastroparesia, el íleo paralítico, los abscesos intraabdominales, las sepsis graves y las hemorragias intra y/o extraluminales (8). La tasa de fístula pancreática clínicamente relevante varía de un 10-30% de los casos según las series (9-11), si bien la tasa global puede ser de hasta un 50% de los casos (8,11). La tasa de complicaciones globales se cifra en un considerable 36 -50 % (2,7,8,12,13).…”
Section: Resultados De La Duodeno-pancreatectomía Cefálica Convencionunclassified
“…Many studies have compared PJ with PG, and a consensus over the most effective technique remains to be determined; although several reports have shown similar outcomes between the 2 manoeuvres, [18][19][20][21] others have found that PG reduces the incidence of postoperative fistula. [22][23][24] Given the overwhelming preference for PJ over PG, quality evidence supporting a single technique has the potential to drastically change the postoperative course for patients undergoing PD.…”
Section: Discussionmentioning
confidence: 99%